To find the amount of change \( c \) that Mela receives, we can set up the equation based on the total amount she gives and the cost of the shoes:
The equation can be represented as: \[ c + 40.99 = 50 \]
This means that her change \( c \) plus the cost of the shoes (which is $40.99) equals the amount she gave to the cashier (which is $50).
To solve for \( c \): \[ c = 50 - 40.99 \] \[ c = 9.01 \]
So, Mela receives $9.01 in change.
The correct response is: c + 40.99 = 50; Mela receives $9.01 in change.